1999
DOI: 10.1126/science.285.5435.1923
|View full text |Cite
|
Sign up to set email alerts
|

Synergy Between Tumor Suppressor APC and the β-Catenin-Tcf4 Target Tcf1

Abstract: Mutations in APC or beta-catenin inappropriately activate the transcription factor Tcf4, thereby transforming intestinal epithelial cells. Here it is shown that one of the target genes of Tcf4 in epithelial cells is Tcf1. The most abundant Tcf1 isoforms lack a beta-catenin interaction domain. Tcf1(-/-) mice develop adenomas in the gut and mammary glands. Introduction of a mutant APC allele into these mice substantially increases the number of these adenomas. Tcf1 may act as a feedback repressor of beta-catenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
333
1
4

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 421 publications
(353 citation statements)
references
References 45 publications
15
333
1
4
Order By: Relevance
“…Possible differences which could explain the reduced Tcf activity in some cell lines include increased expression of corepressors like groucho and CtBP, decreased expression of coactivators like p300 and CBP, acetylation or phosphorylation of Tcf4 preventing ␤-catenin binding or DNA binding, and increased activity of the ⌬N-Tcf1 negative feedback loop. 16,30 Luciferase reporter assays showed a systematic inhibition of Tcf-dependent transcription by E1A. Mutagenesis of E1A indicated that this effect was partly due to inhibition of p300 by E1A, consistent with reports that p300 is a coactivator for ␤-catenin.…”
Section: Comparison Of Different Viruses Showssupporting
confidence: 85%
See 1 more Smart Citation
“…Possible differences which could explain the reduced Tcf activity in some cell lines include increased expression of corepressors like groucho and CtBP, decreased expression of coactivators like p300 and CBP, acetylation or phosphorylation of Tcf4 preventing ␤-catenin binding or DNA binding, and increased activity of the ⌬N-Tcf1 negative feedback loop. 16,30 Luciferase reporter assays showed a systematic inhibition of Tcf-dependent transcription by E1A. Mutagenesis of E1A indicated that this effect was partly due to inhibition of p300 by E1A, consistent with reports that p300 is a coactivator for ␤-catenin.…”
Section: Comparison Of Different Viruses Showssupporting
confidence: 85%
“…12 Cytoplasmic ␤-catenin enters the nucleus, where it can associate with members of the Tcf/Lef family of transcription factors and activate transcription of wnt target genes, such as c-myc, cyclin D1, Tcf1 and matrilysin. [14][15][16][17] Other groups have used Tcf promoters to regulate the expression of suicide genes. 18,19 We placed Tcf binding sites in the adenovirus E2 promoter, which regulates expression of the viral replication genes, because mutations elsewhere in the virus or cell cannot bypass the absolute requirement for E2 gene products in viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid identification of new target genes for HMG domain factors (44,45,46,47,48,49,50,51), it becomes increasingly clear that these factors need to be discriminative for DNA binding. All HMG box factors bind to a common core DNA motif roughly comprising The top three lines represent the binding motifs of Rox1 and Ste11 as deduced by comparison of multiple target promotor sites (26,27,28) and the binding motifs of Sry and Sox-5 as deduced via site selections (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, it appeared that TCF/LEF proteins complexed solely with ␤-catenin to activate gene targets of Wnt signaling, but it is now clear that additional proteins (such as Groucho or C-terminal binding protein) can interact with the complex to modify-even reverse-its effect on transcription Cavallo et al, 1998;Daniels and Weis, 2005). Transcripts of TCF/LEF genes are also prone to alternative splicing, resulting in multiple protein isoforms with potential functional diversity (Roose et al, 1999;van Noort and Clevers, 2002). During animal development, TCF/LEF expression is involved in such diverse functions as establishing embryonic body plans, specification of cell fates, and controlling cell proliferation and survival.…”
Section: Introductionmentioning
confidence: 99%